2018
DOI: 10.3389/fmicb.2018.03136
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cattle, a Potential Reservoir of Human Campylobacteriosis: Epidemiological and Molecular Characterization of Campylobacter jejuni From Cattle Farms

Abstract: Campylobacter jejuni is a major foodborne pathogen that is increasingly found worldwide and that is transmitted to humans through meat or dairy products. A detailed understanding of the prevalence and characteristics of C. jejuni in dairy cattle farms, which are likely to become sources of contamination, is imperative and is currently lacking. In this study, a total of 295 dairy cattle farm samples from 15 farms (24 visits) in Korea were collected. C. jejuni prevalence at the farm level was 60% (9/15) and at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 44 publications
7
47
1
Order By: Relevance
“…Consistent with previous reports, the MLST data confirmed that Campylobacter is genetically diverse, with C. jejuni isolates being more diverse than C. coli (Kinana et al, 2007;Wang et al, 2011;Ngulukun et al, 2016). The dominant CCs in this study were CC-21 and CC-45 and were in agreement with prior findings from other countries in which CC-21 and CC-45 appear to be the largest complexes (Sheppard et al, 2010;Guyard-Nicodème et al, 2015;An et al, 2018). The prevalence of CC-353, CC-464, and CC-828 was lower than those in other regions of China (Zhang et al, 2017), supporting the idea that Campylobacter subtype diversity may differ by region and sampled area.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports, the MLST data confirmed that Campylobacter is genetically diverse, with C. jejuni isolates being more diverse than C. coli (Kinana et al, 2007;Wang et al, 2011;Ngulukun et al, 2016). The dominant CCs in this study were CC-21 and CC-45 and were in agreement with prior findings from other countries in which CC-21 and CC-45 appear to be the largest complexes (Sheppard et al, 2010;Guyard-Nicodème et al, 2015;An et al, 2018). The prevalence of CC-353, CC-464, and CC-828 was lower than those in other regions of China (Zhang et al, 2017), supporting the idea that Campylobacter subtype diversity may differ by region and sampled area.…”
Section: Discussionsupporting
confidence: 92%
“…derived from other sources. Because of the high genetic diversity of C. jejuni mentioned above, differences in the virulence/survival profiles of C. jejuni have been observed in most previous studies for the same host, and even in studies of livestock in the same farm (Young et al, 2007;An et al, 2018). However, the presence or absence of virulence/survival genes in all isolates from this study was similar, except for the virB11 gene.…”
Section: Discussionsupporting
confidence: 43%
“…Similarly, if a single C. jejuni isolate from wild mice captured in one sesame field did not harbor this gene, then no isolates from wild mice captured in that field harbored the gene (Table 2). VirB11, which is present on the pVir plasmid encoding a type-IV secretion system, is involved in horizontal gene transfer and is easily transferred between strains (Juhas et al, 2008); in the case of livestock, its distribution tendency has been found to be similar for the same farm (An et al, 2018). Therefore, the distribution of the virB11 gene in this study suggests that horizontal transmission of C. jejuni may occur frequently among M. minutus that share the same habitat.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations